2021
DOI: 10.1073/pnas.2009620118
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic ATP loss underlies a metabolic combination therapy tailored for MYCN -amplified neuroblastoma

Abstract: MYCN-amplified neuroblastoma is a lethal subset of pediatric cancer. MYCN drives numerous effects in the cell, including metabolic changes that are critical for oncogenesis. The understanding that both compensatory pathways and intrinsic redundancy in cell systems exists implies that the use of combination therapies for effective and durable responses is necessary. Additionally, the most effective targeted therapies exploit an “Achilles’ heel” and are tailored to the genetics of the cancer under study. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Patients with advanced metastatic disease or unsuitable for surgery usually undergo treatment with cisplatin-based agents but are highly susceptible to chemoresistance [ 16 ]. Combination studies using AZD3965 demonstrated that this drug is able to enhance radiosensitivity [ 26 ] but also significantly impairs tumor growth in combination with other agents when compared to the effect of either drug alone [ 36 , 38 , 54 ]. Thus, we combined AZD33965 with cisplatin and evaluated their efficacy in impairing cell viability and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced metastatic disease or unsuitable for surgery usually undergo treatment with cisplatin-based agents but are highly susceptible to chemoresistance [ 16 ]. Combination studies using AZD3965 demonstrated that this drug is able to enhance radiosensitivity [ 26 ] but also significantly impairs tumor growth in combination with other agents when compared to the effect of either drug alone [ 36 , 38 , 54 ]. Thus, we combined AZD33965 with cisplatin and evaluated their efficacy in impairing cell viability and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, growing evidence suggests a major interest in pursuing the study of mitochondria biology in cancer and targeting this organelle therapeutically [ 37 ]. There are multiple ongoing clinical trials exploring the therapeutic effects of Oxidative Phosphorylation (OXPHOS) inhibitors in different tumor types [ 38 ]. Many preclinical studies have suggested anti-tumor activity of ETC CI inhibitors, for instance, metformin, the most common anti-diabetic drug [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting MCTs was proven to significantly suppress the growth or metastasis of solid tumors, like breast cancer, lung carcinoma, and glioblastoma ( Payen et al, 2020 ; Sandforth et al, 2020 ). Inhibitors of MCT4 are in the discovery phase and AZD3965 (a selective inhibitor) is already in the pre-clinical trials to treat cancers ( Dalton et al, 2021 ; Wang et al, 2021 ). Particularly, previous studies have already indicated that MCT1 was an unfavorable factor in RCC ( Guo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%